The time for beginning of enteral nutrition in traumatic shock - Rao, Hui-qing; Mo, Bei-xi; Zhou, Dun-rong; Su, Yue-nan; Jiang, Yue; Lin, Zhi-tao (Zhongguo wei zhong bing ji jiu yi xue, 2006)
To explore the value of monitoring CO(2) partial pressure of gastric mucosa (PiCO(2)) in patients with traumatic shock under enteral nutrition (EN) support. Ninety-six patients who were clinically diagnosed as having traumatic shock were randomly divided into two groups: the test group and the control group. In the test group, EN was given after tissue oxygenation, indicated by the value of PiCO(2), approached normal and the clinical symptoms ameliorated. In control group EN was given at the early stage of recovery from shock. The course of convalescence of the primary disease, gastro-intestinal symptoms, the monitoring indexes, and the complications etc. were compared between the two groups. Acute physiology and chronic health evaluation II (APACHE II) scores were both gradually lowered in both groups. It was more significant in the control group than that in the test group 5 days later (both P<0.01). Compared with the control group, the cure rate in the test group was increased obviously (91.3% vs. 75.0%, P